Meckel's mesodiverticular band causing an internal hernia - Inês Pessanha; Marianna Scuglia; Jorge Correia-Pinto; Rúben Lamas-Pinheiro (Elsevier, 2020)
An 8-year-old boy visited the emergency department due to bilious vomiting and colicky abdominal pain for 3 days. No past surgical or trauma history was declared. On physical examination the child presented with distension and global abdominal tenderness. The blood tests were normal. Ultrasound was negative for acute appendicitis and the CT scan showed a conglomerate of multiple intestinal loops.An urgent laparoscopic exploration was performed to obtain the correct diagnosis. On exploration, the patient had a sac on the right upper abdominal quadrant formed by a mesodiverticular band with distended bowel loops within. As the vascularity of herniated loops had not been compromised, we were able to reduce the hernia contents and excise the mesodiverticular band. The Meckel's diverticulum was then exteriorized, and an extracorporeal resection was performed. Postoperative recovery was uneventful.